Diagnosis of acromegaly: state of the art. (September 2013) - Kannan, Subramanian; Kennedy, Laurence
Abstract : Introduction: Biochemical diagnosis of acromegaly relies on measurement of insulin-like growth factor-1 (IGF-1) and growth hormone (GH). An elevated IGF-1 level above the age- and gender-specific normal range and nonsuppression of GH to oral glucose load to a nadir < 0.4 ng/ml in sensitive assays are currently considered diagnostic of acromegaly. Lack of normative data for both IGF-1 and GH across a wide range of populations and ethnicities, interassay and intraassay laboratory variability, pulsatility of GH secretion, and effects of medications and hormones may confound interpretation of these biochemical tests. Areas covered: Clinical situations in which acromegaly should be suspected and/or investigated. Strengths and limitations of current IGF-1/GH assays are discussed. Clinical scenarios with discordant GH suppression test and IGF-1 levels and, briefly, acromegaly in pregnancy, prolactin-cosecreting tumors, familial acromegaly, and nonpituitary acromegaly are also discussed. Expert opinion: Serum IGF-1 is the cornerstone and in most cases the stand-alone test in the diagnosis and follow-up in patients with acromegaly. Diagnosis depends on the accurate and reliable measurement of serum IGF-1. GH suppression testing is currently used in limited clinical setting. Standardization of IGF-1 assay and development of normative data across a wide population base are needed. Newer bioassays for IGF-1 hold promise for future.